2002
DOI: 10.1002/cncr.10508
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, carboplatin, and topotecan in the treatment of patients with small cell lung carcinoma

Abstract: BACKGROUNDThe objective of this study was to evaluate the feasibility, toxicity, and efficacy of a novel three‐drug regimen containing paclitaxel, carboplatin, and topotecan followed by oral etoposide in the first‐line treatment of patients with small cell lung carcinoma.METHODSOne hundred five patients with previously untreated, limited stage or extensive stage small cell lung carcinoma were treated in this multicenter, community‐based, Phase II trial. All patients received paclitaxel 135 mg/m2 by 1‐hour intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…18 Similarly, in a trial evaluating the combination of paclitaxel, carboplatin, and topotecan in extensive and limited stage disease, 8% of patients had treatment-related death from sepsis. 19 More specifically, of 12 patients with an ECOG performance status of 2, the treatment-related mortality was 42%. The aforementioned 2006 trial by Hanna et al reported a treatment-related death rate of 5.8%.…”
Section: Discussionmentioning
confidence: 98%
“…18 Similarly, in a trial evaluating the combination of paclitaxel, carboplatin, and topotecan in extensive and limited stage disease, 8% of patients had treatment-related death from sepsis. 19 More specifically, of 12 patients with an ECOG performance status of 2, the treatment-related mortality was 42%. The aforementioned 2006 trial by Hanna et al reported a treatment-related death rate of 5.8%.…”
Section: Discussionmentioning
confidence: 98%
“…Triplet regimens that include ifosfamide, topotecan or paclitaxel have been studied in the frontline setting. 2630 The paclitaxel, etoposide and carboplatin regimen was compared to carboplatin, etoposide, and vincristine in a phase III clinical trial. The study enrolled a total of 608 evaluable patients and demonstrated reduced risk of death with the addition of paclitaxel (HR 1.22, 95%CI: 1.03–1.45; P =0.024).…”
Section: Management Of Newly Diagnosed Sclcmentioning
confidence: 99%
“…27 Across a large number of randomized trials, the improved efficacy with dose intensification was attained at the cost of increased toxicity and mortality. 26,28,29,3134 This factor has weighed heavily against widespread adoption of this strategy in the management of SCLC.…”
Section: Management Of Newly Diagnosed Sclcmentioning
confidence: 99%
“…Hainsworth et al [34] /day] on days 1-4 of a 21-day cycle) in patients with extensive SCLC resulted in a more favorable median survival time of 12 months and a 1-year survival rate of 50% [35]. However, five (7%) of the safety-evaluable patients (each with a PS score = 2) died of treatment-related complications.…”
Section: Triplet Regimensmentioning
confidence: 99%
“…The triplet regimen used by Hainsworth et al [34] has also been combined with radiation therapy in patients with limited-stage SCLC [36], where it produced a complete response (CR) rate of 51% and an actuarial median survival time of 20 months. However, severe hematologic toxicities occurred in most patients, hospitalization for febrile or severe neutropenia was required in 11 (14%) patients, and there were three (4%) treatment-related deaths.…”
Section: Triplet Regimensmentioning
confidence: 99%